MORPHOLOGICAL, PHYSICAL AND CHEMICAL CHARACTERIZATION OF SOME SOILS REPRESENTING THE NORTHERN STATES OF THE SUDAN - Thembinkosi, Tshabalala; Deng, Pio Kur; Marchelo-d’Ragga, Philip Wani (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Sixty six soil samples of soils from the Northern states of Sudan were selected from three different locations namely, Elkhalag, Ed Debba, and Merowe to represent the Abu Gidian, Wadi Sherife, Muckabra and El-Eammer soils. The objectives of this study were to characterize these soils’ morphological, physical and chemical properties. Physical and chemical properties were analyzed according to standard procedures, used at the laboratory of Land and Water Research Centre, Agricultural Research Corporation Wad Medani, Sudan. Results showed that all the soils were characterized by a coarse texture (48% to 61%, sand fraction). Abu Gidian; Wadi Sheriff Soil occupies flat to nearly flat land (slope ≤ 1%) with sandy and gravelly material on the surface. They are deep and excessively drained having strong brown 7.5 YR5/6, to reddish color 7.5YR6/6 colour. Muckabrab soil occupies gently sloping to undulating ridges, covered with gravels, calcium carbonate concretion, and stone. Muckabrab soil is moderately deep to shallow and having yellowish colour 10YR5/6 to light yellowish brown color while El-Dammer soil occupies flat to nearly desert plains and has gravel surface. El-Dammer soil is deep and has dark yellowish brown 10YR4/4 to olive colour 2.5Y4/4. The soil is described as light and falls under sandy loam and sandy clay loam. The bulk density (1.3 to 1.5 Mg∙m−3), low organic-C content (0.08% to 0.25%), Alkalinity soil reaction (varied from 7.7 to 8.8). The cation exchange capacity values ranged from 15 to 31 cmol kg -1. The total nitrogen and available phosphorus are low ranged from 0.02 to 0.07% and 2.3 to 3.0 mg kg-1 soil respectively.